2005
DOI: 10.1021/jp054908t
|View full text |Cite
|
Sign up to set email alerts
|

High Conversion Synthesis of Pyrene End Functionalized Polyrotaxane Based on Poly(ethylene oxide) and α-Cyclodextrins

Abstract: We describe the quantitative synthesis of new pyrene labeled cyclodextrin-based polyrotaxane starting from pseudopolyrotaxane of alpha,omega-dimethacrylate poly(ethylene oxide) (PEO) and alpha-cyclodextrins (alpha-CDs). Using a solvent mixture (H2O/dimethyl sulfoxide (DMSO)), an almost quantitative conversion in polyrotaxane can be achieved using the coupling reaction between methacrylic functions and 1-pyrene butyric acid N-hydroxysuccinimide ester. This result is due to the fast blocking reaction of the pseu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
85
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(90 citation statements)
references
References 20 publications
5
85
0
Order By: Relevance
“…As shown in Table 1, 72% of the PEG chains is covered by CDs in DNFB-PR2000 and probably also in APR2000, whereas the inclusion ratios of DNFB-PR3350 and APR35000 are 52% and 25-30%, respectively. Since the polyrotaxane molecules with a high inclusion of CDs are known to become rigid [36,37], DNFB-PR2000 and APR2000 molecules possess the most rigid molecular conformation and relatively large excluded volume among the samples in the present study, resulting in the facile formation of a three-dimensional network when contacted via intermolecular hydrogen bonding in DMSO. A more detailed investigation on the persistence lengths of these polyrotaxanes (for example, with static light scattering measurements) might be performed, although it seems to be problematical due to the abovementioned aggregation only below a polyrotaxane concentration of 1% and gelation at a concentration of 2.5%.…”
Section: Resultsmentioning
confidence: 98%
“…As shown in Table 1, 72% of the PEG chains is covered by CDs in DNFB-PR2000 and probably also in APR2000, whereas the inclusion ratios of DNFB-PR3350 and APR35000 are 52% and 25-30%, respectively. Since the polyrotaxane molecules with a high inclusion of CDs are known to become rigid [36,37], DNFB-PR2000 and APR2000 molecules possess the most rigid molecular conformation and relatively large excluded volume among the samples in the present study, resulting in the facile formation of a three-dimensional network when contacted via intermolecular hydrogen bonding in DMSO. A more detailed investigation on the persistence lengths of these polyrotaxanes (for example, with static light scattering measurements) might be performed, although it seems to be problematical due to the abovementioned aggregation only below a polyrotaxane concentration of 1% and gelation at a concentration of 2.5%.…”
Section: Resultsmentioning
confidence: 98%
“…less, it can be seen that the usual peak of PEG at 3.40-3.50 ppm in DMSO-d 6 was shifted upfield compared with the case of the blank triblock copolymer without adding a-CDs, ascribed to restricted mobility of the polymer chain inside the molecular tube formed by the cyclodextrin rings. 37 It clearly indicated that the target PRs had been successfully synthesized via the ATRP of HPMA in aqueous media.…”
Section: Atrp Of Hpma Initiated With Pprs Comprising Brib-f127-ibbr Amentioning
confidence: 96%
“…The aim of this work is to optimize a grafting reaction of large groups on PEO chain ends which could be applied to the synthesis of polyrotaxane starting from a pseudopolyrotaxane containing PEO. [11] The blocking of the cyclic moieties of such a macromolecular assembly by large groups preventing polymer dethreading by steric hindrance is a challenge. To improve the yield of the polyrotaxane synthesis, the grafting reaction must be fast enough to prevent dethreading.…”
Section: Introductionmentioning
confidence: 99%